ANALYZE RELATIONSHIPS MANGROVE DENSITY AND GASTROPOD ABUNDANCE IN KAYU ARA PERMAI VILLAGE SUNGAI APIT SUBDISTRICT SIAK DISTRICT RIAU PROVINCE - Wanda Syahrian; Zulkifli Zulkifli; Efriyeldi Efriyeldi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The research was conducted on August 2017 in mangove ecosystem of Kayu Ara Permai Village Sungai Apit Sub-district Riau Province. This research aims to analyze mangrove density, the type and abundance of gastropod and relationships between mangrove density, organic content in sediment and gastropod abundance. The method used in this research was survey method. Sampling mangrove species was conducted with line transect plot and sampling organic content and gastropods by using 1 x 1 m2 quadrant plot. The result showed that mangrove density in Kayu Ara Permai varied from 1733-3533 ind/ha. The gastropod abundance varied from 3.67-13 ind/m2, organic content in sediment varied from 0.20-0.13%, diversity index (H’) 0.5-1.12, dominance index (C) 0.52-0.69 and evenness index (E) 0.24-0.52. Relationships between mangrove density and gastropod abundance were 43.20%, relationships mangrove density and organic content in sediment were 18.65%. While relationships between organic content and gastropod abundance were 15.79%.Key Words: Kayu Ara Permai, mangrove density, organic content and gastropod abundance